How ligands and signalling proteins affect G-protein-coupled receptors' conformational landscape. (29th January 2013) - Mary, Sophie; Fehrentz, Jean-Alain; Damian, Marjorie; Verdié, Pascal; Martinez, Jean; Marie, Jacky; Banères, Jean-Louis
Abstract : The dynamic character of GPCRs (G-protein-coupled receptors) is essential to their function. However, the details of how ligands and signalling proteins stabilize a receptor conformation to trigger the activation of a given signalling pathway remain largely unexplored. Multiple data, including recent results obtained with the purified ghrelin receptor, suggest a model where ligand efficacy and functional selectivity are directly related to different receptor conformations. Importantly, distinct effector proteins (G-proteins and arrestins) as well as ligands are likely to affect the conformational landscape of GPCRs in different manners, as we show with the isolated ghrelin receptor. Such modulation of the GPCR conformational landscape by pharmacologically distinct ligands and effector proteins has major implications for the design of new drugs that activate specific signalling pathways.